10t+t+t-t-t=10

Simple and best practice solution for 10t+t+t-t-t=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10t+t+t-t-t=10 equation:


Simplifying
10t + t + t + -1t + -1t = 10

Combine like terms: 10t + t = 11t
11t + t + -1t + -1t = 10

Combine like terms: 11t + t = 12t
12t + -1t + -1t = 10

Combine like terms: 12t + -1t = 11t
11t + -1t = 10

Combine like terms: 11t + -1t = 10t
10t = 10

Solving
10t = 10

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '10'.
t = 1

Simplifying
t = 1

See similar equations:

| (4(y-6))/3=-2y | | -4(-m-5)-7=-11 | | 0=4p-28 | | x+10=x+90 | | 1/2x+5=1/2x-3 | | 5(p-6)=8p-21 | | -(9m+10)+2= | | 8u-8u+u-1=5 | | 12+2n=5n | | 7-5(x+8)=43 | | 8c+2b= | | 4(k+6)=56 | | -5x=3x+6 | | 9p-5p-9-2p=10 | | 6a-16=2(a-6) | | 16=6ty | | 16=6tyv | | 3.045+3b=2.73b+2.4+0.7b | | 8n+22=3 | | -7/2=-6/5x-7/3 | | 5+6p=41 | | -12/k=-4 | | 1(2x-4)=2(4-6x) | | 13/20-1/6 | | 18+6m=5+(-4m) | | 3(x-3)=6x-6-3x | | 70-42y-y=0 | | -12=4-n | | 5e+15=4e+8 | | 3x+3y=102 | | 1x/9 | | 1/2(2x-4)=2(4-6x) |

Equations solver categories